THE REPRESENTATIONS OF GREG GARRARDS ECOCRITICISM CONCEPTS IN DONT LOOK UP MOVIE - Ana Shofiana Jamilah; Abdul Ayiz (Universitas Duta Bangsa Surakarta, 2024)
The relationship between humans and nature serves as a pivotal theme in literature and film, often mirroring societal concerns about the environment and offering profound insights into the dynamics between humanity and the natural world. Adam McKay’s film Don’t Look Up prominently explores this theme. This study employs Greg Garrard’s ecocritical framework to conduct a qualitative descriptive analysis of the film. The primary objective is to investigate how the film portrays environmental issues such as pollution, wilderness, apocalypse, dwelling, and animal, as outlined in Garrard’s ecocritical theory. By closely examining the film's monologues, dialogues, and scenes, this research seeks to uncover the nuances of these themes and their implications for contemporary environmental discourse.